An Energy‐Efficient One‐Pot Swelling/Esterification Method to Prepare Cellulose Nanofibers with Uniform Diameter. Issue 21 (17th October 2018) - Song, Yang; Chen, Wei; Niu, Xun; Fang, Guigan; Min, Huihua; Pan, Hui
Abstract: An energy‐efficient method has been developed to prepare 3–5 nm‐wide carboxyl‐functionalized cellulose nanofibers (CNFs) from pulp fiber by a simple one‐pot swelling followed by esterification process. Tetrabutylammonium acetate (TBAA)/dimethyl sulfoxide (DMSO) binary solvent is used as the swelling agent and the esterification medium admixed with maleic anhydride. All steps are performed at room temperature and no post‐mechanical treatment is needed. The highly efficient defibrillation of pulp fiber to CNFs is thought to be due to two factors: 1) swelling in TBAA/DMSO effectively loosens the structure of cellulose supermolecules by breaking the intra‐ and intermolecular hydrogen bonds between cellulose chains; and 2) the carboxyl groups grafted onto the cellulose molecules by esterification prohibit the reformulation of hydrogen bonds between cellulose chains and therefore stabilize the disperse CNFs with uniform diameter in solution. Other than acid anhydride, no catalyst is added for the esterification, which facilitates the recycling and reuse of the binary solvent. This energy‐efficient one‐pot method could facilitate the large‐scale manufacture of bio‐based nanomaterials. Abstract : Swell did you evah ! 3–5 nm wide cellulose nanofibers have been prepared from pulp fiber by a simple one‐pot swelling/esterification method in tetrabutylammonium acetate (TBAA)/dimethyl sulfoxide (DMSO) binary solvent. All steps are performed at room temperature and no catalyst or post‐mechanical treatment are needed. The strong hydrogen bond forming ability of TBAA/DMSO is believed to play a key role in this remarkably energy‐efficient process.